2004
DOI: 10.1093/carcin/bgh177
|View full text |Cite
|
Sign up to set email alerts
|

Fat and K-ras mutations in sporadic colorectal cancer in The Netherlands Cohort Study

Abstract: Associations between dietary intake of various fats and specific K-ras mutations in colorectal cancer (CRC) were investigated within the framework of The Netherlands Cohort Study on diet and cancer (NLCS). After 7.3 years of follow-up and with exclusion of the first 2.3 years, 448 colon and 160 rectal cancer patients and 2948 subcohort members (55-69 years at baseline) were available for data-analyses. Mutation analysis of the K-ras gene was performed on all archival colon and rectal adenocarcinoma specimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
6
36
0
Order By: Relevance
“…The products of the bile acid excretion may act as tumour promoters by a nonspecific effect that increases cell proliferation in the mucosa layer (Norat et al, 2002). However, total fat intake (Brink et al, 2004) as well as total fresh meat consumption was not associated with overall colon and rectal cancer risk nor with K-ras mutation status. In the previous study (Brink et al, 2004), only o-6 polyunsaturated fat (PUFA) was observed to be associated with specific K-ras mutations; however, this type of fat is not predominantly present in meat.…”
Section: Discussionmentioning
confidence: 79%
“…The products of the bile acid excretion may act as tumour promoters by a nonspecific effect that increases cell proliferation in the mucosa layer (Norat et al, 2002). However, total fat intake (Brink et al, 2004) as well as total fresh meat consumption was not associated with overall colon and rectal cancer risk nor with K-ras mutation status. In the previous study (Brink et al, 2004), only o-6 polyunsaturated fat (PUFA) was observed to be associated with specific K-ras mutations; however, this type of fat is not predominantly present in meat.…”
Section: Discussionmentioning
confidence: 79%
“…44 Indeed, the association with vitamin B2, a cofactor in folate metabolism, 30 tended to be stronger than the association with calcium in our study, and organochlorines, that none of the aforementioned studies assessed, were associated with K-ras mutations in other tumours. 44 Inconsistent findings were also observed regarding other factors, including consumption of red meat, 26,28,29,38,43 and intake of fat 26,29,40,42 and folate. 29,39,42 Other factors have been studied less frequently, [27][28][29]41,42,45 and coffee and tea, whose many constituents exert strong effects upon a wide variety of physiological, cellular and molecular systems, 46 have not been studied in relation to K-ras mutations in adenomas before.…”
Section: Discussionmentioning
confidence: 92%
“…Whereas in vivo and in vitro studies indicate that specific exposures are associated with specific K-ras mutations, [11][12][13][14][15]17,18,44 the general picture regarding associations between exposure and specific K-ras mutations obtained from observational studies is also not clear. 20,26,29,[38][39][40]45 Besides small sample sizes, the inconsistent findings of epidemiological studies on K-ras mutations in colorectal tumours may be partly due to the use of questionnaires to assess exposure. Such an assessment may not be sensitive enough to detect associations; assessment of specific agents hypothesized to affect K-ras mutations, including N-nitroso compounds, 11,12,14 polycyclic aromatic hydrocarbons, 13 heterocyclic amines, 17 n-3 polyunsaturated fatty acids 18 and organochlorine compounds 44 in body fluids or tissue samples may be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory findings of an increased MUFA consumption being associated with a higher prevalence of K-RAS wildtype neoplasia in a study assessing adenomas (453 wildtype, 81 mutated) (Wark et al, 2006) challenges the observation made by Bautista and co-workers. Other published reports have failed to identify any link between K-RAS mutation status and MUFA intake (Brink et al, 2004;Laso et al, 2004;Naguib et al, 2010;Slattery et al, 2000;.…”
Section: K-ras Mutation and Fat Consumptionmentioning
confidence: 98%
“…In addition to these observations, one report describes an increase in polyunsaturated fatty acids (PUFA), specifically linoleic acid, as associated with increased prevalence of K-RAS mutated colonic, but not rectal, cancers (Brink et al, 2004). However, this association with PUFA has not been identifed in any other report (Bautista et al, 1997;Laso et al, 2004;Naguib et al, 2010;Slattery et al, 2000;Wark et al, 2006).…”
Section: K-ras Mutation and Fat Consumptionmentioning
confidence: 99%